Effectiveness of iron supplementation for children with iron deficiency anemia: Study in Purbalingga, Central Java - Febriani, Tien Budi; Choironi, Emy Azmi; Hanum, Latifah (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Background: Iron Deficiency Anaemia (IDA) is one of major factors for human health, especially young children. Iron supplementation can indicate a good response in haemoglobin concentration. Objective: This study is to observe prevalence of anaemia and effectiveness of iron supplementation for children in Purbalingga district, Central Java. Methods: This study was a quasi-experimental study by measuring haemoglobin concentration before (pre) and after (post) treatment. Its participants were determined by a purposive sampling method. 64 children (less than 5 years old) were included in criteria of anaemia. Their blood samples were collected before the treatment to measure SI (Serum Iron) and TIBC (Total Iron Binding Capacity). Administering 4 mg of iron per kg of body weight per day was conducted for a month. Data of participants such as age, nutritional status, socio-demographic, and medical history were also collected. A paired t-test was used to analyse mean differences of haemoglobin levels before and after treatment. Results: Among the 64 children with anaemia, 98.4% indicated Iron Deficiency (ID) with 59.4% of them indicating IDA based on level of SI and TIBC. Anaemia has more prevalence in group of 6 - <12 months of age. There was a statistically significant increase of haemoglobin level with a mean difference of 1.52 g/dL between the pre and post treatment (p=0.000). Conclusion: The prevalence of IDA in children (less than 5 years old) in Purbalingga District Hospital was 59.4%. Adequately oral iron supplementation for a month indicated a statistically significant increase of haemoglobin levels